Uncertain Governance and Resilient Subjects in the Risk Society - O'Malley, Pat (Oñati Socio-Legal Series, 2013)
Over the past decade or so, a series of new or revitalisedstrategies have been promoted to govern the highly uncertain threats that risk appears no longer able to prevent. Most owe their ascendancy to the lessons of 9/11, and the ‘bureaucratising of imagination’ that US sources have proposed as a response, by centring the possible, or even merely imaginable, rather than the statistically probable. Precaution, preparedness and speculative pre-emption have been particularly prominent, although new hybrid statistical and speculative techniques have broadened risk techniques to cope with labile conditions of high uncertainty. But while diverse, each establishes a negative and defensive framework of ‘freedom from’ that has been associated with creating a ’neurotic subject’. In the past decade, programs of resilience, and particularly resiliency training, have been developed with the aim of creating subjects able to thrive and prosper under conditions of extreme uncertainty. They constitute a form of governance promoting a positive ‘freedom to’. Reflecting many of the assumptions and goals of neo-liberal politics, resiliency has already emerged as a principal technology for military and business, and may be the answer to the neo-liberal dream of a society of extreme entrepreneurs.